Analysis of Rice Paddy Farming Income in Pasar Terusan Village, Muara Bulian District, Batanghari Regency - Afifah Suti Nasution, Haura; Ernawati HD, Ernawati HD; Yanita, Mirawati (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2025)
The purpose of this study was to: 1) describe the description of lowland rice farming; and 2) analyze the income of lowland rice farming in Pasar Terusan Village. The selection of respondents was 40 respondents from 4 farmer groups. Data analysis in this study used descriptive analysis with an income formula. The results showed that 1) The description of lowland rice farming in Pasar Terusan Village was 0.30 ha, the seed varieties most widely used Karya Renda and Anak Daro with a usage of 2-8 kg/ha/MT, the types of drugs used were gramaxone, regent, CBA and insecticides with a usage of 0.67-1.57 liters/ha/MT. The types of fertilizers used were Urea, SP36 and KCl with a usage of 8-16 kg/ha/MT, the number of workers used was 1-2 people. The highest amount of lowland rice production was in the Payo Kering I farmer group, which was 1,100 kg/ha/MT. 2) Income of paddy farming in Pasar Terusan Village is Rp.9,813,974,-/ha/MT with revenue of Rp.11,683,750,-/ha/MT and total production cost of paddy farming in Pasar Terusan Village is Rp.1,869,776,-/ha/MT, and from the results of the R/C ratio analysis of 6.25 (R/C> 1) indicates that farmers' income is profitable and feasible to be cultivated. Based on this, this study is expected to be a reference or guideline for farmers in managing their farming businesses, where farmers can improve farming management according to the conditions of the land they have by utilizing all inputs to produce production or produce output according to the wishes of farmers.